Fondrako dalam Perspektif Epistemologi Budaya dan Teologi Kontekstual dan Implikasinya bagi Pembinaan Jemaat - Angilata Kebenaran Halawa; Novi Sariaharita; Vivi Ivana Gunawan; Martinus Duryadi; Junihot M. Simanjuntak (SANCTUM DOMINE: JURNAL TEOLOGI, 2026)
Studies on customary law within the context of Christianity often fall into two opposing tendencies: the total rejection of local culture or its uncritical acceptance without theological evaluation. Within this debate, the Nias customary law Fondrako has rarely been examined as a cultural epistemology with constructive potential for church formation. This study aims to explore the cultural epistemology embedded in Fondrako and to critically reinterpret it within the framework of contextual theology in order to identify its relevance for the formation of church members. This research employs a qualitative approach through library research using a descriptive-analytical method. The findings reveal that Fondrako functions not only as the highest customary legal system in Nias but also as a source of epistemological values shaping social order, ethical norms, and communal life. From the perspective of contextual theology, the encounter with Christianity has transformed the application of Fondrako, shifting it from punitive and curse-based sanctions toward values grounded in biblical principles of love, justice, and reconciliation. This study argues that the epistemological values embedded in Fondrako, including discipline, social solidarity, deliberation, reconciliation, and restorative justice—can be critically and theologically integrated as a contextual model for church formation. It, therefore, positions contextual theology as an approach that neither rejects local culture nor accepts it uncritically, but rather interprets and transforms it in the light of the Gospel to foster mature faith, character, and communal life within the church.